Challenge of diagnosing pyoderma gangrenosum after caesarean section. Issue 7 (27th July 2019) - Foessleitner, Philipp; Just, Ulrike; Kiss, Herbert; Farr, Alex
Abstract : Pyoderma gangrenosum is a neutrophilic skin disease that leads to extensive, painful, necrotic ulcerations, particularly at surgical sites. As obstetric cases with pyoderma gangrenosum are rare and, therefore, often misdiagnosed initially, it is important to raise awareness about this rare complication. Here, we describe a patient who presented with pyoderma gangrenosum at the surgical site 4 days after undergoing a caesarean section. The erythema was initially misdiagnosed as wound infection, and the patient, who was experiencing pain, underwent antibiotic treatment and surgical wound debridement. When the wound was unresponsive to these treatments, a dermatologist was consulted who suspected pyoderma gangrenosum and began a high-dose corticosteroids therapy, which led to a fulminant improvement of the local wound. In conclusion, the rare diagnosis of pyoderma gangrenosum should be considered in the differential diagnosis of a suspected surgical wound infection. Early interdisciplinary treatment is essential to avoid further complications.